Classificação de linhagens de milho em grupos heteróticos baseados em microssatélites e análise dialélica para rendimento, óleo e proteína - Ferreira, Fernando Rafael Alves (2012)
The combing ability of the available genotypes is the main criterion to determine the potential of maize breeding programs aimed to the hybrids development. The aim of this study was to estimate the combining ability and the genetc diversit of 12 lines of maize developed by Syngenta Seeds Ltda. using microsatellite molecular markers. The lines were crossed in a diallel model and evaluated in experiments designrd in complete blocks with randomized complete block design with two replications, carried out in two location of the state of Parana, Brazil. The following characteristics were evaluated: (i) grain yield in kg ha-1, with correction for moisture, (ii) crude protein percentage, (iii) oil content percentage. Genetic diversity was assessed using 20 polymorphic microsatellite primers. For all characteristics studied, the mean squares of the diallel were significant for all treatments, indicating the existence of genetic variability between line. The general combining abilities were significant for all traits. The specific capabilities were significant for protein content and grain yield. The interaction between the general and specific capabilities occurred only for grain. The line PD620 contracted by the high general combining ability (ĝi ) for grain yield in both environments. The line PD391 and PD620 were found relevant for grain yield in the Cascavel and Mauá da Serra respectively. For protein contented, the line that stood out with the Gi was PF771. For the oil contented, the line that presented the best value for the Gi was PD620. The hybrid combinations associated with higher grain estimates were: HD128 x SD462, HD128 x PF771, HD128 x SF241 e HD128 x SF076, because those presented at least one parent with positive estimate of GCA. For the percentage of crude protein, the crosses that stood out for the Sij estimate were SF241 x PD317 and PD620 x PF771. Through the analysis of microsatellites, an arrangement of six distinct goups with a solid formation and little mixing was observed, In which the line HD733 is represented by a single group. A formation of a sub-dented heterotic group with the lines PD412 and SD462 occurred. The line PD620 contracted by the high general combining ability (ĝi)for protein content, oil content and grain yield in both locations. The line PD391 and SF241 were found relevant for grain yield in the Cascavel and Mauá da Serra respectively. For protein contented, the line that stood out with the ĝi was PF771. For the oil contented, the line that presented the best value for the ĝi was PD620. The hybrid combinations associated with higher grain estimates were: HD128 x SD462, HD128 x PF771, HD128 x SF241 e HD128 x SF076, because those presented at least one parent with positive estimate of GCA. For the percentage of crude protein, the crossing that stood out was to estimate the PD620x PD317. Through the analysis of microsatellites, an arrangement of six distinct groups with a solid formation and little mixing was observed, In which the line HD733 is represented by a single group. A formation of a sub-dented heterotic group with the lines PD412 and SD462 occurred.